Prioritas Pengembangan Usaha Mikro, Kecil dan Menengah (UMKM) Sektor Non-Unggulan Provinsi Jawa Tengah - Andryan Setyadharma; Rahma Wijayanti; Karmelia A.N. Fauzin; M. Lutfi Febryansyah (Pusat Penelitian Pemberdayaan Fiskal dan Ekonomi Daerah (P3FED) Universitas Papua, 2018)
One way to find out regionals’ potentials is by calculating location quotient (LQ) in order to identify basic sectors of regions. Previous studies have shown that policy advices given were to pay attention on the basic sectors to improve the regional economy, with less discussion on non-basic sectors. The aims of this study are: (1) to access whether there are trickle down effects from basic to non basic sectors based on LQ calculation, (2) determine non basic and sub sectors of Micro, Small and Medium Enterprises (MSMEs) to be prioritized for development based on Central Java Province’s Medium Term Development Planning. LQ calculations during 2010 to 2016 period show that from 17 economic sectors in Central Java, education services sector was the only sector that a non-basic sector in 2010 and became a basic sector in 2016. LQ results also show that four sectors have always been basic sectors and eight sectors have always been non-basic sectors, the two sectors had changed but returned as before in the next year and two sectors changed from basic sectors to non-basic sectors. This study suggests that Central Java government should pay attention to the non-basic sectors of MSMEs in order to improve the economy of Central Java.